2022
DOI: 10.1039/d1ce01487k
|View full text |Cite
|
Sign up to set email alerts
|

Long-range supramolecular synthon polymorphism: a case study of two new polymorphic cocrystals of Ph2Te2–1,4-C6F4I2

Abstract: Along with the reported earlier co-crystal of diphenyl ditelluride (Ph2Te2) and halogen bond donor 1,4-diiodo-tetrafluorobenzene (p-DITFB) 1α, its two new polymorphic forms (1β and 1γ) present a rare case of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…27 In our recent studies of the co-crystallization of diphenyl ditelluride or organometallic halides with the σand π-hole donors, we noted the relationship between the columnar or layered topology of the energy frameworks and the needle or the plate-like habits of the respective crystals. 28,29 In order to corroborate these relationships in the molecular co-crystals, we examined in the current work the associations of the iodo-dihalogens ICl, IBr, and I 2 with aliphatic and aromatic nucleophiles, in particular, 1,4-diazobicyclo[2,2,2]octane, pyridine, 2-bromopyridine, 4-dimethylaminopyridine and phenazine (abbreviated hereinafter as DABCO, Py, PyBr, PyNMe 2 and Phnz, respectively).…”
Section: Introductionmentioning
confidence: 98%
“…27 In our recent studies of the co-crystallization of diphenyl ditelluride or organometallic halides with the σand π-hole donors, we noted the relationship between the columnar or layered topology of the energy frameworks and the needle or the plate-like habits of the respective crystals. 28,29 In order to corroborate these relationships in the molecular co-crystals, we examined in the current work the associations of the iodo-dihalogens ICl, IBr, and I 2 with aliphatic and aromatic nucleophiles, in particular, 1,4-diazobicyclo[2,2,2]octane, pyridine, 2-bromopyridine, 4-dimethylaminopyridine and phenazine (abbreviated hereinafter as DABCO, Py, PyBr, PyNMe 2 and Phnz, respectively).…”
Section: Introductionmentioning
confidence: 98%
“…This approach offers accurate computation of intermolecular interaction energies between molecular pairs in crystal structures and their visualization using colored cylinders, 37,41 and has been shown to be particularly useful in the analysis of weak interactions, such as hydrogen, halogen and chalcogen bonds. [42][43][44][45][46][47] These cylinders represent the energies between molecular pairs in crystals; the thicker the cylinder, the higher the interaction energy. Contributions of different types of intermolecular interactions (electrostatic, dispersion, polarization, repulsion) can be determined for each interacting molecular pair.…”
Section: Crystal Packingmentioning
confidence: 99%
“…From the perspective of crystal engineering, drug–drug multicomponent crystals provide an effective method to solve the problems of FDCs. Drug–drug multicomponent crystals refer to multicomponent solid crystalline supramolecular complexes composed of two or more APIs in the same lattice interacting through interactions . Due to the specific interactions in the crystal lattice, the physicochemical properties of the parent drugs may be improved, such as improving the dissolution behavior of at least one API, , enhancing the stability of unstable APIs, , which are expected to solve the dilemma of FDCs and further promote the bioavailability and therapeutic effect of the drug. Moreover, studies have shown that drug–drug multicomponent crystals are an effective route to accelerate the development of the drug from preclinical studies to approved drugs. , For instance, the drug–drug multicomponent crystal product Entresto has a synergistic effect of 1 plus 1 greater than 2, which was approved by the US Food and Drug Administration (FDA) in 2015 for the treatment of chronic heart failure. , …”
Section: Introductionmentioning
confidence: 99%